Functional interleukin-4 releasing microparticles impact THP-1 differentiated macrophage phenotype - Lee, I-Ning; Stening, Jasmine Z.; Rose, Felicity R. A. J.; White, Lisa J. (Frontiers in Bioengineering and Biotechnology, 2024)
Macrophage cell therapies offer potential treatment in inflammatory diseases due to their ability to mobilize and stimulate their environment. However, successful treatment requires a pro-regenerative macrophage phenotype to be retained in vivo. Polymeric microparticles may provide a potential route to direct and sustain macrophage phenotype. Interleukin-4 (IL-4) is the most commonly used cytokine for in vitro modulation towards M2a macrophage phenotype. We designed interleukin-4 (IL-4) encapsulated microparticles to investigate the impact of drug release kinetics and developed a robust THP-1 in vitro assay to assess functional IL-4 release upon macrophage phenotype. Microparticles, fabricated from PLGA and a PLGA-PEG-PLGA triblock copolymer were encapsulated with IL-4 and human serum albumin (HSA) for sustained release. IL-4 release kinetics fit with the first-order release kinetics model, indicating concentration dependent release. IL-4/HSA encapsulated microparticles modulated human peripheral blood monocyte cell (THP-1) differentiated macrophages towards pro-immunoregulatory subgroups. This strategy provides a novel approach in drug carrier development and for in vitro assessments of macrophage phenotype to inform development of targeted therapies for inflammation and immune modulation.